Analisis Penilaian Ekonomi Gumuk Pasir Parangtritis di Kecamatan Kretek, Kabupaten Bantul, DIY - Khatimah, Khusnul; Syaukat, Yusman; Ismail, Ahyar (Jurnal Ekonomi dan Pembangunan Indonesia, 2017)
Sand dunes is an unique beach-forest phenomenon which only in Southeast Asia can be found in Parangtritis Village. In the existing condition, sand dunes might have direct use value and indirect use value, even though these benefits do not applied in the entire area. The research aims is to estimate the economic value of sand dunes in the existing condition using total economic valuation (TEV). The result showed that the direct uses are tourism (Rp1,009 million/year), fuel wood (Rp106 million/year), livestock feed (Rp188 million/year), while the indirect uses are abrasion barrier (Rp1,505 million/year), and wind barrier (Rp1,019 million/year). The total economic value of Parangtritis sand dunes up to Rp3,828 million/year.